The prevalence of incidental findings in computed tomography of the head in Pediatric Emergency Department - Lipińska, Justyna; Lipiński, Łukasz; Kopeć, Izabela; Kowalczuk, Maria; Woźniak, Magdalena Maria (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Computed tomography (CT) is the first imaging modality in the evaluation of children in case of patients with head injury in pediatric Emergency Departments (EDs). Radiological CT reports include not only lesions that are the main cause of the child’s complaints but also incidental findings. The objective of this study is to assess incidental findings observed in children who were admitted to the ED and had the head CT performed. Material and methods. This retrospective, cross-sectional study enrolled 644 children under the age of 18, from 1st January 2021 to 31st June 2021. Each child could have had one or more incidental findings in CT Results. Among all CT studies, incidental findings were found in 279 out of 644 (43.32%) cases, of which 73 (11.34%) had both lesions detected incidentally and related to the trauma. Conclusion. Head CT is an incredibly useful tool in the assessment of some head emergencies. However, evaluation of the prevalence of incidental findings is difficult. Most of them require no specific further investigation. Pediatricians, who order CTs in children, must be prepared to interpret and communicate findings to families and introduce treatment in necessary situations.
The study was conducted in accordance with the Declaration of Helsinki. In accordance with the law in force in the Republic of Poland, retrospective studies do not require the opinion or consent of the Bioethics Committee, as they are not a medical experiment in which human organisms would be interfered with. For this reason, we did not seek the consent of the Commission. What’s more, the results of the study did not affect the management of patients at any stage, so the above-mentioned procedure was followed.
Keywords: head CT incidental findings; pediatric ED; pediatric head CT